From Scrolling to Awareness: How @zerowaste.id_official’s Insta Campaign Shapes Gen Z Eco-Consciousness - Wanna Zahara; Febri Nurrahmi (JKG (Jurnal Komunikasi Global))
Awareness of the importance of environmental preservation can be effectively cultivated through social media. One example is the zero waste campaign that uses Instagram to reduce the use of single-use plastics. This study aims to analyze the influence of the zero waste campaign on the Instagram account @zerowaste.id_official on the environmental awareness of students at Syiah Kuala University. The study adopts Kotler's model, specifically the learn, feel, do model. The research method used is explanatory quantitative, with surveys distributed through Google Forms to 133 students at Syiah Kuala University who have seen content from the Instagram account @zerowaste.id_official. The sampling technique used is quota sampling from each faculty. The research results show that the t-value (5.534) is greater than the t-table value (1.657) with a coefficient of determination of 0.189, meaning the zero waste campaign influences students' environmental awareness by 18.9%. The linear regression result shows a value of b = 0.404 and a significance level of 0.000. In conclusion, the zero waste campaign on the Instagram account @zerowaste.id_official has a positive and significant impact on the environmental awareness of students at Syiah Kuala University. This indicates that the greater the exposure to the campaign, the higher the students' environmental awareness.